2003
DOI: 10.1074/jbc.m305904200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Group V Phospholipase A2 in Caveolin-enriched Granules in Activated P388D1 Macrophage-like Cells

Abstract: In murine P388D 1 macrophages, the generation of prostaglandin E 2 in response to long term stimulation by lipopolysaccharide involves the action of Group V secreted phospholipase A 2 (PLA 2 ), Group IV cytosolic PLA 2 (cPLA 2 ), and cyclooxygenase-2 (COX-2). There is an initial activation of cPLA 2 that induces expression of Group V PLA 2 , which in turn induces both the expression of COX-2 and most of the arachidonic acid substrate for COX-2-dependent prostaglandin E 2 generation. Because Group V PLA 2 is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 28 publications
6
60
1
2
Order By: Relevance
“…Some caveolin-2 is found in caveolae, in association with caveolin-1, but even in these cases, most of the caveolin-2 detected by immunofluorescence resides in the Golgi complex (45)(46)(47). A recent study showed co-localization of human group V sPLA 2 with caveolin-2 in punctate domains in the macrophage-like cell line p388D1 (49). Given the above concerns, the localization of human group V sPLA 2 in caveolae is called into question.…”
Section: Localization Of Hgiia In Hek293 Cells By Immunofluorescence-mentioning
confidence: 99%
See 2 more Smart Citations
“…Some caveolin-2 is found in caveolae, in association with caveolin-1, but even in these cases, most of the caveolin-2 detected by immunofluorescence resides in the Golgi complex (45)(46)(47). A recent study showed co-localization of human group V sPLA 2 with caveolin-2 in punctate domains in the macrophage-like cell line p388D1 (49). Given the above concerns, the localization of human group V sPLA 2 in caveolae is called into question.…”
Section: Localization Of Hgiia In Hek293 Cells By Immunofluorescence-mentioning
confidence: 99%
“…Given the above concerns, the localization of human group V sPLA 2 in caveolae is called into question. Treatment of cells with extracellular heparin reduces the amount of immunofluorescence staining of hGIIA and group V sPLA 2 in punctate domains (21,49), and this is cited as evidence that the punctate localization of sPLA 2 derives from re-entry of extracellular enzyme. It may be noted that heparin treatment did not eliminate punctate staining (49).…”
Section: Localization Of Hgiia In Hek293 Cells By Immunofluorescence-mentioning
confidence: 99%
See 1 more Smart Citation
“…This led to characterizing the eicosanoids produced downstream of PLA 2 and their autocrine and paracrine function in lipid signaling in the cellular milieu (99 -101). This all became considerably more complex as we realized that the activation of eicosanoid synthesis could involve activation of multiple PLA 2 s (102)(103)(104)(105)(106) stimulated by the products of other PLA 2 s from distinct subcellular locations (107,108).…”
Section: A Turning Point For Lipid Signalingmentioning
confidence: 99%
“…The observations that GV sPLA 2 can hydrolyze Gram-negative bacterial phospholipids (6) and that phagocytosis by peritoneal macrophages is modulated by GV sPLA 2 (7) suggests that GV sPLA 2 participates in the killing of bacteria by leukocytes (5). GV sPLA 2 can be expressed by macrophages (7,8), mast cells (9,10), airway smooth muscle cells (11), and bronchial epithelial cells (12) in mice and by alveolar macrophages, bronchial epithelial cells, and interstitial fibroblasts in patients with pneumonia, where expression of GV sPLA 2 correlates with the severity of inflammation (13). Overexpression of GV sPLA 2 leads to increased PGE 2 biosynthesis by cultured bronchial epithelial cells (13) and to surfactant degradation, respiratory distress, and neonatal lethality in transgenic mice that constitutively express the enzyme under an actin promotor (14).…”
mentioning
confidence: 99%